Tangeretin alleviates sepsis-induced acute lung injury by inhibiting ferroptosis of macrophage via Nrf2 signaling pathway - Hui Zhang; Yan Wang; Shenghua Wang; Xiaomei Xue; Kai Huang; Dunfeng Xu; Lai Jiang; Siyuan Li; Yunqian Zhang (Chinese Medicine)
Abstract Background Sepsis-induced acute lung injury (ALI) is a severe clinical condition accompanied with high mortality. Tangeretin, which is widely found in citrus fruits, has been reported to exert antioxidant and anti-inflammatory properties. However, whether tangeretin protects against sepsis-induced ALI and the potential mechanisms remain unclear. Methods We established an ALI model via intraperitoneally injected with 5 mg/kg lipopolysaccharides (LPS) for 12 h. Tangeretin was applied intraperitoneally 30 min before LPS treatment. Dexamethasone (Dex) was used as a positive control. Hematoxylin and eosin (HE) staining and protein content in bronchoalveolar lavage fluid (BALF) were determined to detect the degree of lung injury. RNA-seq was also applied to explore the effect of tangeretin on ALI. In vitro, RAW264.7 were treated with Nrf2 siRNA, the expression of ferroptosis-associated biomarkers, including glutathione peroxidase 4 (GPX4) and prostaglandin-endoperoxide synthase 2 (PTGS2) were assessed. Glutathione (GSH), malondialdehyde (MDA) levels, reactive oxygen species (ROS) and inflammatory factors were also determined both in vivo and in vitro. Furthermore, mice were treated with an Nrf2 inhibitor (ML385) to verify the mechanism of tangeretin in inhibiting sepsis-induced lung injury and ferroptosis. Data were analyzed using one way analysis of variance or two-tailed unpaired t tests. Results Our study demonstrated that tangeretin significantly alleviated lung injury, reversed the LPS-induced reduction in GPX4 and GSH, and mitigates the elevation of PTGS2 and MDA levels. Tangeretin also reduced 4-HNE and iron levels. Besides, the levels of LPS-stimulated inflammatory factors IL-6, IL-1β and TNF-α were also decreased by tangeretin. RNA-seq and bioinformatics analysis demonstrated that tangeretin inhibited inflammatory response. Mechanistically, we identified that tangeretin inhibited the GPX4-dependent lipid peroxidation through activation of Nrf2. The silence of Nrf2 abolished the inhibitory effect of tangeretin on oxidative stress, inflammatory response and ferroptosis in RAW264.7 cells. Additionally, all the protective effects of tangeretin on ALI were abolished in Nrf2 inhibitor-treated mice. Conclusion We identified that ferroptosis as a critical mechanism contributing to sepsis-induced ALI. Tangeretin, a promising therapeutic candidate, effectively mitigates ALI through inhibiting ferroptosis via upregulating Nrf2 signaling pathway.